Electrodeposition model with dynamic ion diffusion coefficients for predicting void defects in electroformed microcolumn arrays - Ma, Zhigao; Jiang, Bingyan; Dong, Yanzhuo; Qiang, Jun; Drummer, Dietmar; Zhang, Lu (Physical Chemistry Chemical Physics, 2023)
Due to the confined mass transfer capability in microchannels, void defects are easily formed in electroformed microcolumn arrays with a high depth/width ratio, which seriously affects the life and performance of micro-devices. The width of the microchannel constantly decreases during electrodeposition, which further deteriorates the mass transfer capability inside the microchannel at the cathode. In the traditional micro-electroforming simulation model, the change of the ion diffusion coefficient is always ignored, making it difficult to accurately predict the size of void defects prior to electroforming experiments. In this study, nickel ion diffusion coefficients in microchannels are tested based on the electrochemical experiments. The measured diffusion coefficients decrease from 4.74 × 10−9 to 1.27 × 10−9 m2 s−1, corresponding to microchannels with a width from 120 to 24 μm. The simulation models of both constant and dynamic diffusion coefficients are established, and the corresponding simulation results are compared with the void defects obtained using micro-electroforming experiments. The results show that when the cathode current densities are 1, 2 and 4 A dm−2, the size of void defects obtained with the dynamic diffusion coefficient model is closer to the experimental results. In the dynamic diffusion coefficient model, the local current density and ion concentration distribution proves to be more inhomogeneous, leading to a big difference in the deposition rate of nickel between the bottom and the opening of a microchannel, and consequently a larger void defect in the electroformed microcolumn arrays. In brief, the ion diffusion coefficient inside microchannels with a different width is tested experimentally, which provides a reference for developing reliable micro-electroforming simulation models.
CRIS-Team Scopus Importer:2023-03-17